Ru-based catalyst for plasma coupled catalytic ammonia cracking as well as preparation method and application of Ru-based catalyst
The Ru-based catalyst prepared by ultrasonic impregnation method solves the problems of poor activity and poor stability of existing catalysts under medium and low temperature conditions, and achieves high-efficiency ammonia cleavage at low temperatures, which improves the ammonia conversion rate and the stability of the catalyst.
Patent Information
- Application Number
- CN202411667014.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing Ru-based catalysts have poor catalytic activity and poor stability under medium and low temperature conditions, and are prone to sintering and inactivation under high temperature conditions, resulting in low hydrogen production efficiency of ammonia cracking.
The Ru-based catalyst was prepared by ultrasonic impregnation method. Catalysts were prepared by stirring at room temperature, ultrasonic stirring at 40°C, vacuum drying, grinding, oxidation and calcining, and catalysts with low loading of active metal Ru, high dispersion and good stability were prepared.
High-efficiency ammonia cleavage under low temperature conditions is achieved, and the ammonia conversion rate reaches more than 90%, reducing the reaction temperature and energy consumption, and extending the activity and stability of the catalyst.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of ammonia cracking hydrogen production technology, and specifically relates to a catalyst for low-temperature plasma coupled catalytic ammonia cracking, and a preparation method and application thereof. Background Art
[0002] In recent years, with the continuous consumption of traditional non-renewable fossil energy sources such as coal, oil, and natural gas, problems such as energy shortage and environmental deterioration have become increasingly prominent. Based on this, the transformation from traditional energy to new energy is imminent, and hydrogen energy, as a highly efficient renewable energy source, has attracted much attention from researchers. As an energy "porter", hydrogen is widely used in transportation, industry, and power production due to its advantages such as abundant sources, high energy density, flexible storage and transportation, and single and clean combustion products. It plays an important role in promoting sustainable development strategies. However, in practical applications, the storage and transportation process of hydrogen has problems such as low efficiency, high cost, and poor safety, which greatly limits the widespread use of hydrogen energy. In order to solve the above problems, some researchers have proposed the use of appropriate media to realize the storage and transportation of hydrogen. The hydrogen storage density of ammonia is 121kg-H2 / m 3 It is safer in storing and transporting hydrogen. It is an ideal carrier that can not only store and transport hydrogen in a green and efficient manner, but also quickly decompose and produce hydrogen.
[0003] At present, in the traditional thermal catalytic ammonia cracking reaction, the cracking temperature of ammonia is usually above 550°C, which requires a lot of energy. For example, Chinese patent document CN116390893A discloses a Co-based catalyst for ammonia decomposition, and Chinese patent document CN105013519B discloses a Ru-based catalyst for ammonia decomposition. Both patents state that the reaction temperature required for ammonia cracking is relatively high and is only applicable to traditional thermal catalytic ammonia cracking. In addition, metal catalysts are prone to sintering at higher reaction temperatures, which leads to reduced activity or even deactivation. In order to solve the problem of poor low-temperature activity of catalysts in traditional thermal catalytic processes, the present invention provides a catalyst suitable for thermal catalysis, pure plasma catalysis, and thermal catalysis + plasma catalysis coupled ammonia cracking, and realizes efficient ammonia cracking under low temperature conditions. The catalyst proposed in the present invention has high selectivity for plasma-activated reaction substances, which is beneficial to improving the conversion rate of low-temperature plasma-coupled catalytic ammonia cracking hydrogen production reaction. In summary, the catalyst can greatly reduce the reaction temperature and effectively reduce the reaction energy consumption, making it possible to decompose ammonia at room temperature. It provides a feasible way for the application of NH3 in on-board hydrogen and hydrogen-ammonia mixed combustion power generation, and plays an important role in promoting the rapid development of hydrogen energy. Summary of the invention
[0004] The technical problem solved by the present invention is to alleviate the high cost of Ru-based catalysts and the defects of poor catalytic activity and stability under medium and low temperature conditions, thereby providing a method for preparing a catalyst for hydrogen production by cracking ammonia with low active metal Ru loading, high dispersion and good stability.
[0005] Another technical problem solved by the present invention is to overcome the problem that the efficiency of Ru-based catalysts for hydrogen production by ammonia cracking is low under medium and low temperature conditions, and the catalysts are easily sintered and deactivated under high temperature conditions, thereby providing a low-temperature and efficient ammonia cracking hydrogen production technology.
[0006] The technical solution of the present invention is to provide a low-temperature and high-efficiency method for preparing a Ru-based catalyst for plasma-coupled catalytic ammonia cracking to produce hydrogen. The steps of preparing the catalyst by ultrasonic impregnation are as follows:
[0007] Step 1: dissolving a certain amount of active metal Ru salt hydrate and a carrier in an appropriate amount of ultrapure water, and stirring them for 30 minutes at room temperature to obtain a metal salt mixed solution for preliminary impregnation;
[0008] Step 2: Stir the obtained metal salt mixed solution for 20 to 30 minutes at a temperature of 40°C and an ultrasonic power of 60W to fully immerse the mixed solution;
[0009] Step 3: Transfer all the mixed solution that has been fully impregnated to a vacuum drying oven, dry it at 105°C for 2-4 hours, take it out and put it in a mortar, and grind it into a fine powder;
[0010] Step 4: evenly spread the powdered solid on a culture dish, and place it in a blast drying oven at 70-75°C for 4-6 hours to fully oxidize it;
[0011] Step 5: Transfer the completely dried catalyst to a muffle furnace, start from room temperature, heat at a rate of 10°C / min to the calcination temperature, and maintain this temperature for 2 to 4 hours. After calcination, cool naturally to room temperature;
[0012] Step 6: Grind and sieve the calcined catalyst so that the particle size of the catalyst particles is 200-300 meshes.
[0013] Furthermore, the active metal component Ru accounts for 0.1-10% of the total mass fraction of the catalyst, and its preparation raw material is ruthenium chloride hydrate (RuCl3·3H2O).
[0014] Furthermore, the carrier accounts for 77.5-97.5% of the total mass fraction of the catalyst, and its raw material is nitrate hydrate Ce(NO3)3·6H2O.
[0015] Furthermore, the carrier CeO2 is nitrate hydrate Ce(NO3)3·6H2O calcined at 650°C to form the corresponding metal oxide.
[0016] Furthermore, the calcination temperature of the Ru-based catalyst is one of 450°C, 550°C, and 650°C.
[0017] Furthermore, the present invention also provides the above-mentioned Ru-based catalyst for application in different ammonia cracking technologies and reaction conditions, including the following contents:
[0018] (1) Applying the catalyst Ru / CeO2 to thermal catalytic ammonia cracking;
[0019] (2) Applying the catalyst Ru / CeO2 to the ammonia cracking method combined with plasma and thermal catalysis;
[0020] (3) Applying the catalyst Ru / CeO2 to the plasma-catalyzed ammonia cracking method;
[0021] Further, the thermal catalytic ammonia cracking reaction temperature is one or more of 100 to 400°C;
[0022] Furthermore, the plasma power supply discharge power of the plasma combined with thermal catalytic ammonia cracking is one or more of 10 to 50 W and the reaction temperature is 100 to 400° C.;
[0023] Furthermore, the discharge power of the plasma power supply for plasma-catalyzed ammonia cracking alone is one or more of 30-31W, 40-41W, and 50-51W;
[0024] Furthermore, there are four coupling modes between the catalyst and the plasma discharge interval position, namely, the catalyst is completely filled at the front end of the plasma discharge interval position, the catalyst is partially filled at the plasma discharge interval position, the catalyst is completely filled at the plasma discharge interval position, and the catalyst is completely filled at the rear end of the plasma discharge interval position.
[0025] Compared with the existing catalyst and ammonia cracking technology, the present invention has the following advantages:
[0026] (1) The catalyst prepared by the present invention has good low-temperature ammonia cracking activity under the conditions of thermal catalysis, pure plasma catalysis, and thermal catalysis + plasma catalysis, and the ammonia conversion rate can reach more than 90%;
[0027] (2) The active metal Ru loading of the catalyst of the present invention is low, and the cost of the corresponding catalyst is lower;
[0028] (3) The CeO2 carrier used in the catalyst of the present invention can be directly obtained by calcining nitrate hydrate, and the preparation process is simple;
[0029] (4) The catalyst preparation process of the present invention is simple and easy to operate, and does not require a H2 reduction treatment process;
[0030] (5) The Ru-based catalyst prepared by the present invention has a uniform particle size distribution, and the active metal components are highly dispersed on the carrier surface;
[0031] (6) After 36 hours of continuous ammonia cracking reaction, the catalyst of the present invention showed good activity and stability;
[0032] (7) The catalyst of the present invention cooperates with the plasma to effectively improve the conversion rate of the ammonia cracking reaction;
[0033] (8) The activation energy of ammonia cracking by the low-temperature plasma coupled catalyst proposed in the present invention is 20.56-80.2 kJ / mol, which is much lower than the 120-145 kJ / mol reported in the literature. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a dot-line graph of the conversion rate of different Ru-based catalysts used for low-temperature plasma-coupled catalytic ammonia cracking reaction at 100-400°C;
[0035] Figure 2 At 100-400℃, Ru 0.025 / Conversion rate dotted line diagram of CeO2 catalyst for low temperature plasma catalysis and thermal catalytic ammonia cracking;
[0036] Figure 3 In the absence of external heating, Ru 0.025 / CeO2 catalyst for pure plasma-assisted catalyst ammonia cracking conversion point line diagram;
[0037] Figure 4 YesRu 0.025 / Apparent activation energy of CeO2 catalyst for low temperature plasma coupled catalytic ammonia cracking reaction;
[0038] Figure 5 YesRu 0.025 / CeO2 and Ru 0.1 / CeO2 XRD patterns of the two catalysts. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is further described below in conjunction with some embodiments.
[0040] Example 1: Ru 0.01 / CeO2 catalyst
[0041] The raw materials for preparing the catalyst are mainly ruthenium chloride hydrate (RuCl3·3H2O) and cerium oxide (CeO2). Among them, RuCl3·3H2O is used to provide the active metal component of the catalyst, and CeO2 is used as the carrier of the catalyst. The catalyst is prepared by ultrasonic impregnation method, and the operation process is as follows: first, weigh 0.078g of RuCl3·3H2O and 3.031g of CeO2, pour them into a beaker filled with 5mL of deionized water in turn and stir them thoroughly to dissolve them to obtain a mixed solution of metal salts; secondly, the obtained mixed solution of metal salts is continuously stirred by ultra-frequency ultrasound at 40°C and 60W for 20 to 30 minutes to obtain a sufficient impregnation solution; then, take out the impregnation solution and transfer it to a vacuum drying oven, dry it at 105°C for 2 to 4 hours, and after drying, Take it out and pour it into an agate mortar and grind it into fine powder; then, spread the powdered solid evenly on a culture dish and dry it in a forced air drying oven set at 75°C for 4 to 6 hours to fully oxidize it; then, transfer the dried catalyst to a muffle furnace, start from room temperature, increase the temperature at a rate of 10°C / min to the calcination temperature, and keep the temperature for 2 to 4 hours. After the calcination is completed, cool it naturally to room temperature; finally, grind the treated catalyst again, and obtain a catalyst with a particle size of 200 to 300 mesh by sieving.
[0042] Example 2: Ru 0.025 / CeO2 catalyst
[0043] The same as Example 1, except that in the catalyst preparation process, 0.078g of RuCl3·3H2O is replaced by 0.194g of RuCl3·3H2O, and 3.031g of CeO2 is replaced by 2.925g of CeO2. The catalyst preparation method is the same as Example 1.
[0044] Example 3: Ru 0.05 / CeO2 catalyst
[0045] The same as Example 1, except that in the catalyst preparation process, 0.078g of RuCl3·3H2O is replaced by 0.388g of RuCl3·3H2O, and 3.031g of CeO2 is replaced by 2.85g of CeO2. The catalyst preparation method is the same as Example 1.
[0046] Example 4: Ru 0.1 / CeO2 catalyst
[0047] The same as Example 1, except that during the catalyst preparation process, 0.078 g of RuCl3·3H2O was replaced by 0.776 g of RuCl3·3H2O, and 3.031 g of CeO2 was replaced by 2.7 g of CeO2. The catalyst preparation method was the same as Example 1.
[0048] Comparative Example 1: Ru 0.025 / CeO2 catalyst
[0049] The same as Example 2, except that in the catalyst preparation process, the metal oxide calcined with Ce(NO3)3·6H2O is selected as the Ru-based catalyst carrier. The catalyst preparation method is the same as Example 1.
[0050] Comparative Example 2: Ru 0.025 / ZSM-5 catalyst
[0051] The same as Example 2, except that during the catalyst preparation process, 2.925 g of CeO2 was replaced by 2.925 g of ZSM-5. The catalyst preparation method was the same as Example 2.
[0052] Comparative Example 3: Ru 0.025 / Al2O3 catalyst
[0053] The same as Example 2, except that during the catalyst preparation process, 2.925 g of CeO2 was replaced by 2.925 g of Al2O3. The catalyst preparation method was the same as Example 2.
[0054] Comparative Example 4: Ru 0.025 / La2O3 catalyst
[0055] The same as Example 2, except that during the catalyst preparation process, 2.925 g of CeO2 was replaced by 2.925 g of La2O3. The catalyst preparation method was the same as Example 2.
[0056] Comparative Example 5: Ru 0.025 / Pr6O 11 catalyst
[0057] Same as Example 2, except that during the catalyst preparation process, 2.925 g of CeO2 was replaced by 2.925 g of Pr6O 11The preparation method of the catalyst is the same as that of Example 2.
[0058] Application examples:
[0059] Ru 0.025 / CeO2 catalyst is used for low temperature plasma coupled catalytic ammonia cracking reaction. The application steps are as follows: Before the test, weigh 0.5g of Ru 0.025 / CeO2 catalyst and 0.5g CeO2 solid, fully mix to obtain a total mass of 1g catalyst, fill the catalyst completely in the discharge interval of the corundum tube, and fix it with quartz wool; continue to introduce argon gas with an inlet flow rate of 30mL / min into the plasma fixed bed reactor for 10min to exhaust the residual air in the reactor. After the preparation work is completed, turn on the reaction device and plasma power supply, and introduce pure ammonia gas with an inlet flow rate of 30mL / min into the reactor to test the plasma coupled catalytic ammonia cracking reaction. Among them, the discharge power of the plasma power supply is maintained at 30-31W, the reaction temperature starts at 100℃, the step length is 50℃, and the temperature is programmed at a rate of 10℃ / min. The reaction time at each temperature point (100℃, 150℃, 200℃, 250℃, 300℃, 350℃, 400℃) is maintained for 30min. During the reaction, an ammonia flowmeter is used to record the inlet flow of ammonia in real time. The unreacted ammonia is absorbed by dilute sulfuric acid with a mass fraction of 20%. The flow of hydrogen and nitrogen produced by cracking is recorded in real time using a mixed flowmeter (the molar ratio of N2 and H2 is 1:3).
[0060] Ru 0.025 / CeO2 catalyst is used for thermal catalytic ammonia cracking reaction, and its application steps are the same as low-temperature plasma coupled catalytic ammonia cracking reaction, the difference is that no plasma power supply is required.
[0061] Ru 0.025 / CeO2 catalyst is used for pure plasma catalytic ammonia cracking reaction. Its application steps are the same as low-temperature plasma coupled catalytic ammonia cracking reaction. The difference is that no additional temperature is required.
[0062] In order to test the activity of the catalyst in the low-temperature plasma coupled catalytic ammonia cracking reaction, the conversion rate of ammonia was used. The apparent activation energy Ea (kJ / mol) parameters are evaluated and the calculation formula is as follows:
[0063]
[0064] Among them, F in Indicates the inlet flow rate of ammonia, in mL / min; F out Indicates the outlet flow rate of the hydrogen and nitrogen mixed gas in mL / min.
[0065]
[0066] Wherein, A represents the pre-exponential factor; R is the thermodynamic constant of an ideal gas, R=8.31441 J / (K·mol); T represents the temperature of the reaction system, in K; Ea is the apparent activation energy of the catalyst, in kJ / mol.
[0067] The calculation results of the conversion rate X of the low-temperature plasma coupled catalytic ammonia cracking reaction under the action of different catalysts prepared in the present invention are shown in the attached figure. Figure 1 shown.
[0068] In the Ru prepared in the present invention 0.025 The calculation results of the conversion rate X of the ammonia cracking reaction under the action of / CeO2 catalyst are as follows Figure 2 and Figure 3 shown.
[0069] The present invention is used for low temperature plasma coupled catalytic ammonia cracking reaction of Ru 0.025 The calculation results of apparent activation energy of CeO2 catalyst are as follows: Figure 4 shown.
[0070] The Ru prepared by the present invention 0.025 / CeO2 and Ru 0.1 The XRD patterns of the two catalysts are shown in Figure 5 shown.
[0071] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A Ru-based catalyst for low-temperature plasma coupled catalytic ammonia cracking to produce hydrogen, characterized in that: The catalyst comprises an active metal component and a carrier, wherein the active metal component is Ru and the carrier is alkaline rare earth oxide CeO2.
2. The specific features of the Ru-based catalyst described in claim 1 are as follows: The active metal component Ru accounts for 0.1-10% of the total mass fraction of the catalyst, and its preparation raw material is ruthenium chloride hydrate (RuCl3·3H2O); The carrier accounts for 77.5-97.5% of the total mass fraction of the catalyst, and its raw material is one or more of nitrate hydrate Ce(NO3)3·6H2O or metal oxide CeO2.
3. The carrier CeO2 according to claim 2, characterized in that: The nitrate hydrate Ce(NO3)3·6H2O was calcined at 650°C to the corresponding metal oxide CeO2.
4. The CeO2 carrier according to claim 2, characterized in that: The particle size and purity of CeO2 are different. The particle size of the best CeO2 carrier is 20-50nm and the purity is 99.5%.
5. The method for preparing the Ru-based catalyst according to any one of claims 1 to 2, wherein the specific steps are as follows: Step 1: dissolving a certain amount of active metal Ru salt hydrate and a carrier in an appropriate amount of ultrapure water, and stirring them for 30 minutes at room temperature to obtain a metal salt mixed solution for preliminary impregnation; Step 2: Stir the obtained metal salt mixed solution for 20 to 30 minutes at a temperature of 40°C and an ultrasonic power of 60W to fully immerse the mixed solution; Step 3: Transfer all the mixed solution that has been fully impregnated to a vacuum drying oven, dry it at 105°C for 2-4 hours, then take it out and put it into a mortar, and grind it into a fine powdery solid; Step 4: evenly spread the powdered solid on a culture dish, and place it in a blast drying oven at 70-75°C for 4-6 hours to fully oxidize it; Step 5: Transfer the completely dried catalyst to a muffle furnace, start from room temperature, heat at a rate of 10°C / min to the calcination temperature, and keep the temperature for 2 to 4 hours. After the calcination is completed, cool it naturally to room temperature. Step 6: Grind and sieve the calcined catalyst so that the particle size of the catalyst particles is 200-300 meshes.
6. The calcination temperature of the Ru-based catalyst according to claim 5, characterized in that: The calcination temperature of the catalyst is one of 450°C, 550°C and 650°C.
7. The Ru-based catalyst suitable for low-temperature plasma coupled catalytic ammonia cracking to produce hydrogen as described in claims 5 to 6, characterized in that: There is no need to use reducing gas (H2 / Ar) to reduce the catalytic material before the reaction.
8. The use of the Ru-based catalysts described in claims 5 to 7 in the fields of thermal catalysis, pure plasma catalysis, and thermal catalysis + plasma catalysis ammonia cracking, characterized in that: Is it necessary to provide additional heat of 100 to 450°C to the plasma reactor? 9. The process conditions for applying the Ru-based catalyst in a plasma environment as claimed in claim 8, characterized in that: The discharge power of the plasma power supply is 10 to 51W.
Citation Information
Patent Citations
A catalyst for ammonia decomposition and its application
CN105013519B
Ammonia decomposition catalyst
CN116390893A
Method for preparing Ni-based catalyst by ultrasonic-assisted impregnation method
CN109759068A
Equipment for producing hydrogen by catalyzing ammonia decomposition through cooperation of plasma and metal oxide and experimental method
CN115636391A
Preparation method of fly ash-based supported catalyst for catalyzing desorption of CO2-rich amine solution
CN117046492A